Kedudukan Hukum Administrasi Negara Dalam Tata Hukum Indonesia - Wahid, Ali Abdul (Universitas Sang Bumi Ruwa Jurai, 2017)
The state of Indonesia is a state of law. As a constitutional state, every governance must be based on the applicable law. In a state of law, the law is placed as a rule of play in the administration of state, government, and society. While the purpose of the state law itself is the creation of statehood activities, government, and society that relies on justice, peace, and usefulness. The existence of State Administration Law is expected to know the limits and essence of power, purpose, and nature rather than obligations, as well as how the forms of sanctions whenever there is a violation of state administration.